Vegetable residue valorization for soil health and climate resilience - Quansah, Kwesi Ewudzie; Asah-Asante, Richard; Xudong, Fan; Xinran, Shen; Ming, Li; Di, Wenjin; Xin, Ma; Jizhong, Wang; Miao, Gao (Frontiers in Soil Science, 2025)
Food waste is a critical global challenge that threatens environmental sustainability. Vegetable residue, a key component, is often disposed through harmful methods such as landfilling and incineration which significantly increase resource loss and degrade the ecological system. Sustainable and eco-friendly valorization techniques are solutions needed to address this challenge. This review explores the valorization of vegetable residue within a circular agriculture framework, emphasizing its potential to enhance soil health, reduce reliance on synthetic fertilizers, and support climate resilience. Vegetable residues, rich in organic matter, can be valorized through composting, vermicomposting, anaerobic digestion, biochar production, direct application, or integrated system (biochar + compost) to produce nutrient-rich soil amendments and renewable energy. These approaches enhance soil fertility, microbial activity, water retention, and carbon sequestration. However, challenges persist, including heavy metal contamination, technical constraints, and adoption barriers. Recent advances, such as microbial inoculants, enzyme-based pretreatment, integrated residue management systems, and emerging AI and low-energy technologies offer promising solutions to address these limitations. This review systematically synthesizes current practices, emerging innovations, and policy frameworks to advance sustainable residue utilization and agricultural transformation.